2010
DOI: 10.1074/jbc.c110.114124
|View full text |Cite
|
Sign up to set email alerts
|

EGF-induced Grb7 Recruits and Promotes Ras Activity Essential for the Tumorigenicity of Sk-Br3 Breast Cancer Cells

Abstract: Co-amplification and co-overexpression of ErbB2 and Grb7 are frequently found in various cancers, including breast cancer. Biochemical and functional correlations of the two molecules have identified Grb7 to be a pivotal mediator downstream of ErbB2-mediated oncogenesis. However, it remains largely unknown how Grb7 is involve in the ErbB2-mediated tumorigenesis. In this study, we show that Grb7-mediated cell proliferation and growth are essential for the tumorigenesis that occurs in ErbB2-Grb7-overexpressing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 27 publications
4
63
0
1
Order By: Relevance
“…Previous studies showed that GRB7 was required for SK-BR-3 cell proliferation and ERK1/2 and Akt phosphorylation [22,23]. Conversely, overexpression of GRB7 and ERBB2 in MCF-7 breast cancer cells enhance ERBB2 and Akt phosphorylation and tumor xenograft growth [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that GRB7 was required for SK-BR-3 cell proliferation and ERK1/2 and Akt phosphorylation [22,23]. Conversely, overexpression of GRB7 and ERBB2 in MCF-7 breast cancer cells enhance ERBB2 and Akt phosphorylation and tumor xenograft growth [24].…”
Section: Discussionmentioning
confidence: 99%
“…A GST-(Raf)-Ras binding domain (RBD) pulldown assay was performed according to the method described previously (14). The RBD of Raf glutathione S-transferase (GST) fusion protein (GST-Raf-RBD) was precoupled with glutathione-Sepharose 4B according to the manufacturer's instructions and then incubated with HKC lysates for 2 h at 4°C to detect GTP-bound Ras-GTPases as described previously.…”
Section: Gst-(raf)-ras Binding Domain Pulldown Assaymentioning
confidence: 99%
“…41 A study showed that GRB7, through its interaction with Ras, resulted in increased ERK1/2 phosphorylation. 42 Our study found that the number of implantation sites and GRB7 protein expression both decreased after antisense oligonucleotide injection. Therefore, we supposed that GRB7 affects embryo implantation by regulating endometrial cell migration; however, its function during embryo implantation is still unclear.…”
Section: Discussionmentioning
confidence: 67%